Patient perspectives on naloxone receipt in the emergency department: a qualitative exploration - Margaret Lowenstein; Hareena K. Sangha; Anthony Spadaro; Jeanmarie Perrone; M. Kit Delgado; Anish K. Agarwal (BMC, 2022)
Abstract Background Emergency departments (EDs) are important venues for the distribution of naloxone to patients at high risk of opioid overdose, but less is known about patient perceptions on naloxone or best practices for patient education and communication. Our aim was to conduct an in-depth exploration of knowledge and attitudes toward ED naloxone distribution among patients who received a naloxone prescription. Methods We conducted semi-structured telephone interviews with 25 adult participants seen and discharged from three urban, academic EDs in Philadelphia, PA, with a naloxone prescription between November 2020 and February 2021. Interviews focused on awareness of naloxone as well as attitudes and experiences receiving naloxone in the ED. We used thematic content analysis to identify key themes reflecting patient attitudes and experiences. Results Of the 25 participants, 72% had previously witnessed an overdose and 48% had personally experienced a non-fatal overdose. Nineteen participants (76%) self-disclosed a history of substance use or overdose, and one reported receiving an opioid prescription during their ED visit and no history of substance use. In interviews, we identified wide variability in participant levels of knowledge about overdose risk, the role of naloxone in reducing risk, and naloxone access. A subset of participants was highly engaged with community harm reduction resources and well versed in naloxone access and use. A second subset was familiar with naloxone, but largely obtained it through healthcare settings such as the ED, while a final group was largely unfamiliar with naloxone. While most participants expressed positive attitudes about receiving naloxone from the ED, the quality of discussions with ED providers was variable, with some participants not even aware they were receiving a naloxone prescription until discharge. Conclusions Naloxone prescribing in the ED was acceptable and valued by most participants, but there are missed opportunities for communication and education. These findings underscore the critical role that EDs play in mitigating risks for patients who are not engaged with other healthcare or community health providers and can inform future work about the effective implementation of harm reduction strategies in ED settings.